Hubungan Kausalitas antara Perkembangan Sektor Keuangan Dengan Volatilitas Ekonomi: Kasus Indonesia, 1990.1 - 2004.2 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT This study investigates the causality relations between financial development and macroeconomic volatility in Indonesia. Besides we try to identify whether the development of both sectors can reduce the existence of macroeconomic volatility. Using the methodology of Granger causality and TodaYamamoto procedure, the result shows that the relationship between financial development and macroeconomic volatility is unidirectional causality. Another evidence indicates the financial development that grows faster will generate the existence of macroeconomic volatility. Prior to causality test, through Engle-Granger, Johansen and Gregory-Hansen test (which includes structural break) reveals there is a cointegration between the variables of financial development with the variable of macroeconomic volatility.